IMPLEMENTATION OF NURSING PROBLEMS WITH IMPAIRED SKIN INTEGRITY IN PATIENTS WITH DIABETES MELLITUS ON THE SDKI AND SIKI : AN EVIDENCE-BASED PRACTICE - Hamidah Sulistyowati; Rizka Lailatul Amalia; Arista Maisyaroh (UNEJ e-Proceeding, 2022)
Background: tissue integrity disorders are the most common symptoms found and complained about by people with Diabetes Mellitus; this occurs due to macroangiopathy that can trigger vascular insufficiency and nerve damage so that if there is pressure/friction, it is easier to cause open wounds on the surface of the skin The purpose of this case study is to find out more specifically significant minor signs and symptoms and interventions based on SDKI and SIKI. Method: This study is a study that uses descriptive analysis from secondary data from the Case Report of the D3 Nursing Study Program, University of Jember, Lumajang Campus, for the period 2018 – 2021. Univariate data analysis was performed to assess major and minor data and establish diagnoses based on SDKI and SIKI. Results: There were a total of 29 Diabetes Mellitus patients. There are major signs of 100% tissue/layer damage to the skin, and two minor signs, namely 79% pain and 72% redness. Eight interventions are often carried out. Namely 100% wound care, 48% health education, collaboration with other medical personnel 41%, infection protection 27%, other activities 20%, and there are additional interventions, namely modern dressing, 27%, and metronidazole compresses 24%. Conclusion: Enforcement of nursing diagnoses and interventions of skin/tissue integrity disorders will be easier to do with the support of the results of clinical evidence-based practices related to major and minor signs and the most effective, efficient and successful interventions based on SDKI and SIKI.